Pemahaman Anatomi Klinis dalam Praktik Dokter Spesialis Kedokteran Fisik dan Rehabilitasi di Jakarta - Sudiyono, Nelson; Liemanto, Hans; Uinarni, Herlina; Djuartina, Tena; Irawan, Robi; Sasmita, Poppy Kristina (Jurnal Kedokteran Meditek, 2026)
Introduction: Anatomical knowledge is a fundamental foundation in the practice of physical medicine and rehabilitation specialists (physiatrists), particularly in diagnosis and medical management. Studies have shown that understanding of anatomy may decline over time, potentially affecting diagnostic accuracy and the success of medical interventions. This has encouraged researchers to investigate the understanding of clinical anatomy in PM&R specialists practice in Jakarta. Purpose: To describe the level of understanding, perception, and application of clinical anatomy in daily PM&R specialists’ practice. Methods: This study was a descriptive study. The respondents were PM&R specialists in Jakarta, with a total sample of 40 participants. Data were collected through electronic questionnaires completed by respondents who met the inclusion criteria. Results: Data collection included an anatomy quiz, with a mean score of 70.9. A total of 52.5% of respondents scored above the mean. The most commonly used anatomy learning methods were clinical-based (50%) and integrative (57.5%). Anatomical knowledge, particularly in physical examination, was applied by 90% of respondents in daily practice. Conclusion: A proportion of respondents demonstrated an adequate level of anatomical knowledge, as they consistently integrate anatomical understanding into daily clinical practice. However, there remains room for improvement through continuing professional development related to clinical anatomy.